Southern Thai High School Students' Anxiety in Speaking Performance - Kusumo, Atmo; Prihatin, Yoga; Aflahatun, Nur (LPPM Universitas Pancasakti Tegal, 2020)
This study is focused on identifying the level of southern Thai high school students' anxiety in speaking performance, describing their attitudes towards oral communication during classroom and evaluating of their proficiency in speaking English, and investigating their reasons for anxiety in a foreign language. The participants of the research were 25 fourth-grade high school students at Koh Lanta Yai, Krabi, Thailand. The present study employed a case study qualitative research design. A questionnaire adapted from the Foreign Language Classroom Anxiety Scale were obtained to investigate average levels of anxiety through three dimensions. Whereas, open-ended questions were obtained to collate students' oral communication attitudes, evaluation of their proficiency in speaking English, and reasons for anxiety in communicating orally. The quantitative analysis indicated that English speaking anxiety exists among southern Thai high school students generally at a moderate level. Qualitatively, students revealed negative attitudes towards communicating orally during the classroom, while half of the interviewed participants reported a negative evaluation of their proficiency in speaking English. Finally, the lack of students' self-confidence was found to be their major reason for anxiety in speaking.